Judicial Jurisdiction in a Federal State - Iraq as a Model – “A Comparative Analytical Study” - Hamid, Abdullah Fadhel (Journal of Legal and Political Studies, 2025)
The research deals with the judicial jurisdiction in Iraq and the Kurdistan Region-Iraq, in comparison with the same jurisdiction in the United States of America. The research aims to clarify the mechanism of distributing judicial jurisdiction in Iraq as a federal state, and it has become clear to us that there is one type of legislative and judicial authorities in the Iraqi region, which is always federal according to the constitutional description, which means the lack of local public authorities, as well as the absence of federal courts in the Kurdistan Region-Iraq whose jurisdiction is to consider disputes arising from the application of federal laws. The research reached a number of conclusions, the most important of which is the existence of internal conflicts of laws in Iraq, which is a conflict arising from the fact that the Kurdistan Region-Iraq has a parliament that issues laws that sometimes differ from the same laws in force in the rest of Iraq, and the personal multiplicity of personal status laws in Iraq raises a conflict between laws stemming from the personal multiplicity of laws. Based on the conclusions reached by the research, a set of recommendations was proposed, the most important of which is the necessity for the Iraqi and Kurdish legislator to establish rules to resolve the problem of internal conflict over legislative and judicial jurisdictions in the country. Keywords: Federal courts, federal laws, legal shopping, forum shopping.
Keywords: Federal courts; federal laws; legal shopping; forum shopping